2016
DOI: 10.1680/jgeot.15.t.026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of a small-scale energy pile in saturated clay

Abstract: International audienceThe mechanical behaviour of an energy pile in saturated clay under thermo-mechanical loading was studied using a model pile. Axial load was first applied to the pile head in steps to determine the resistance of the pile under mechanical load. Afterwards, thermo-mechanical tests were performed by applying a heating/cooling cycle to the pile under constant axial load. The results show pile head heave during heating and settlement during cooling. Irreversible settlement was observed after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 38 publications
3
23
0
2
Order By: Relevance
“…A number of small-scale physical model studies have characterized the axial thermal response of energy piles for monotonic heating (McCartney and Rosenberg, 2011;Ng et al, 2014b;Goode and McCartney, 2015) and cyclic temperatures (Kalantidou et al, 2012;Ng et al, 2014a;Stewart and McCartney, 2014;Yavari et al, 2014Yavari et al, , 2016aNg et al, 2016;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of small-scale physical model studies have characterized the axial thermal response of energy piles for monotonic heating (McCartney and Rosenberg, 2011;Ng et al, 2014b;Goode and McCartney, 2015) and cyclic temperatures (Kalantidou et al, 2012;Ng et al, 2014a;Stewart and McCartney, 2014;Yavari et al, 2014Yavari et al, , 2016aNg et al, 2016;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for the stable responses of the thermal strains towards the end of experiments is that there were no head loads on the pile or end restraints in the present study. According to some physical model studies with thermal cycles on energy piles (Kalantidou et al, 2012;Stewart and McCartney, 2013, Yavari et al, 2014, 2016aWang et al, 2016), thermally induced settlement is reversible for pile head loads corresponding to as low as 20% of the pile ultimate resistance, and becomes irreversible for higher pile loads, particularly for loads closer to the ultimate pile resistance. However, the soil type plays an important role in the thermal response of the pile, and the dense sand at the current site likely contributed to the relatively high resistance to axial thermal deformations.…”
mentioning
confidence: 99%
“…For a saturated clay-concrete interface, Di Donna et al showed an increase of the interface shear strength due to heating, which may be explained by thermal consolidation [12]. Yavari et al showed that the temperature effects on the friction angle and adhesion are minor [13][14] and the results of Xiao et al [11] showed a slight decrease of adhesion of the soil-concrete interface when subjected to cooling and negligible effects on the friction angle for unsaturated soil conditions. Xiao et al [15] also pointed out that after 10.5 temperature cycles an increase of the interface shear strength as well as an increase of adhesion (in the case of large heating cycles) was detected for sandy silty clay-concrete interface and it was mostly attributed to water migration due to the temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the response of the soil-pile interface, Xiao et al, Di Donna et al, and Yavari et al performed direct shear tests to explore the effect of the temperature changes [11][12][13][14] and Xiao et al [15] investigated the effect of temperature cycles on a disturbed natural soilconcrete interface for unsaturated conditions. For a saturated clay-concrete interface, Di Donna et al showed an increase of the interface shear strength due to heating, which may be explained by thermal consolidation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale physical model studies with thermal cycles on energy piles (Kalantidou et al, 2012;Stewart and McCartney, 2014;Yavari et al, 2014Yavari et al, , 2016aWang et al, 2017;Nguyen et al, 2017) have indicated that the thermally induced axial settlement of the pile is reversible for pile head loads corresponding to as low as 20% of the ultimate pile capacity, but becomes irreversible for higher pile head loads closer to the ultimate pile capacity. The field tests conducted by Faizal et al (2018) indicated that the axial and radial thermal responses of an unrestrained energy pile embedded in dense sand followed linear reversible paths for heating and cooling cycles, suggesting that both the pile and the soil did not undergo significant thermally induced deformations.…”
Section: Introductionmentioning
confidence: 99%